Factors Affecting Patient Reported Outcomes after Surgical Fixation for a Lisfranc Injury. Issue 4 (November 2022) - Shah, Ashish; Young, Sean M.; Littlefield, Zachary; Prahad, Srihari R.; Luque-Sanchez, Kevin S.; Reed, Logan; Young, Matthew
Category: Bunion; Other Introduction/Purpose: Hallux valgus is a common deformity the foot and ankle surgeon will encounter that tends to have a progressive nature with a predilection for females. There are many operative techniques to appropriately treat HV however, there is limited literature focused on patient-reported outcomes for these procedures. In particular, we intend to compare patient- reported outcomes for those who had early (2 weeks postoperatively) vs standard weight-bearing (SWB) (6 weeks postoperatively) postoperative protocols after hallux valgus correction via the Lapidus procedure. Methods: A retrospective analysis of patients that underwent hallux valgus correction at our facility from 2010-2021 was conducted. Patients were selected if they underwent this correction via the Lapidus procedure. Basic patient demographics, preoperative and post-operative hallux valgus angles and intermetatarsal angles were recorded, type of hardware used for fixation, postoperative weight bearing protocol, complication rate, deformity recurrence, duration of symptoms, and any adjunctive procedures were all recorded utilizing the electronic medical record. Early weight-bearing (EWB) was defined as beginning a protected weight-bearing protocol at the two week visit. To evaluate outcomes, we utilized the Foot and Ankle Ability Measure (FAAM) survey as well as the Patient Reported Outcomes Measurement Information System (PROMIS) survey. Results: A total of 77 patients met criteria for this study with 20 patients having completed both the FAAM and PROMIS score surveys. The average time point at which the outcomes were collected was 5.65 years postoperatively ranging from 2.43 to 11.5 years. There were 35 patients in the EWB cohort and 42 in the SWB protocol. The average PROMIS physical function, pain interference, and depression scores for the EWB population was 45.96, 54.66, and 47.48 respectively vs 47.10, 48.34, and 50.21 in the SWB group. Patients in the EWB group reported their average activities of daily living (ADLs) via the FAAM subscale to be at 57% vs 62% in the SWB group. For the FAAM Sports Subscale, both groups reported fairly low numbers at 44% and 36% respectively. In this study, 1 patient experienced wound infection, 3 patients experienced nonunion (2 EWB, 1 SWB), and 1 patient experienced deformity recurrence. Conclusion: Preliminary results suggest equivalent results for EWB and SWB postoperative protocol for patients undering the Lapidus procedure. We plan to increase the power of our study for a more thorough investigation as well as conduct a more intensive statistical analysis to gain more insight on patient related factors and their effect on outcomes. We expect a higher number of patients to complete the PROMIS and FAAM surveys as we continue to reach out to these patients.